2020
DOI: 10.21203/rs.3.rs-44042/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cisplatin-Resistant Gastric Cancer Cells Promote the Chemoresistance of Cisplatin-Sensitive Cells via Exosomal RPS3 Mediated PI3K-Akt-cofilin-1 Signaling Axis

Abstract: Background: Cisplatin is an important agent in first-line chemotherapy against gastric cancer (GC). However, consequential drug resistance limits its effectiveness for the treatment of GC. Exosomes which are loaded with proteins, lipids and RNAs, have been proven to transfer malignant phenotype. This study aims to explore the role and mechanism of exosomal RPS3 protein in transmitting a chemoresistance phenotype from cisplatin resistant to cisplatin sensitive gastric cancer cells.Methods: A cisplatin resistant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Furthermore, exosome-mediated molecular transfers decreased the accumulation of loaded ncRNA in nontarget tissues, therefore reducing off-target toxicity [142]. Recently, Sun and coworkers found that chemoresistant GC cells promoted the chemoresistance of chemosensitive GC cells via exosome-mediated substance exchange [143].Inhibiting this substance exchange mediated by exosomes or associated molecules may exert an antitumor role in GC. In 2018, Wand and colleagues found that transferring exosomes carrying anti-miR-214 into GC cells reversed cisplatin resistance [144].…”
Section: Reversing Chemo-resistance By Delivering Ncrnasmentioning
confidence: 99%
“…Furthermore, exosome-mediated molecular transfers decreased the accumulation of loaded ncRNA in nontarget tissues, therefore reducing off-target toxicity [142]. Recently, Sun and coworkers found that chemoresistant GC cells promoted the chemoresistance of chemosensitive GC cells via exosome-mediated substance exchange [143].Inhibiting this substance exchange mediated by exosomes or associated molecules may exert an antitumor role in GC. In 2018, Wand and colleagues found that transferring exosomes carrying anti-miR-214 into GC cells reversed cisplatin resistance [144].…”
Section: Reversing Chemo-resistance By Delivering Ncrnasmentioning
confidence: 99%
“…Platinum drugs are one of the most common chemotherapy drugs used for GC, and cisplatin and oxaliplatin have been included as first-line treatments. Cisplatin-resistant gastric cancer cells communicate with sensitive cells through RPS3 in sEVs and activation of the PI3K-Akt-cofilin-1 signalling pathway [ 98 ]. Zheng et al [ 99 ] found that M2-polarized macrophages can promote resistance to cisplatin in GC cells.…”
Section: The Relationship Between Sevs and Gcmentioning
confidence: 99%
“…Drug resistance is a major clinical problem, which partially leads to poor survival rate of GC patients. 31 However, drug resistance limits its effectiveness for the treatment of GC. Sun et al demonstrated that cisplatin-resistant GC cells derived exosomes enhanced the chemoresistance of cisplatin-sensitive GC cells through exosomal RPS3 mediated PI3K/Akt/cofilin-1 pathway.…”
Section: Exosomes and Drug Resistance In Gcmentioning
confidence: 99%
“…Sun et al demonstrated that cisplatin-resistant GC cells derived exosomes enhanced the chemoresistance of cisplatin-sensitive GC cells through exosomal RPS3 mediated PI3K/Akt/cofilin-1 pathway. 31 Therefore, targeting exosomal RPS3 in cisplatin resistant GC cells may be a promising strategy to overcome cisplatin resistance. The findings of Zheng et al suggested that exosomal transfer of cancer-associated macrophages derived miR-21 mediates cisplatin resistance in GC.…”
Section: Exosomes and Drug Resistance In Gcmentioning
confidence: 99%